Urban population of Volyn region: resettlement and dynamics - Pavlovska, Tetiana Serhiivna; Pohrebskyi, Taras Heorhiiovych; Golub, Gennadii Serhiiovych; Poruchynsky, Volodymyr Ivanovych (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2019)
Introduction. Currently, the spatial and temporal evolution of urban settlement systems has become an important object of the research at the regional, national and global levels. After all, urbanization is a rather complicated process. On the one hand, it is characterized by an increase in the size of the urban population, level of comfort and standard of living, modernization of all spheres of society's life. On the other hand, urbanization is accompanied by tensions regarding the use of basic natural resources, inconsistency in the demands of life comfort from the pace of development of housing and communal services and the planning structure of cities, etc. The study of the spatial and temporal evolution of the urban settlement systems is an important task on the regional, national and global levels. Therefore, the identification of resettlement patterns, the dynamics of urban processes and qualitative characteristics of the urban population, in particular, Volyn region are very relevant and deserve attention of modern geodemographers.The aim of the article is to analyze the settlement of the existing urban population and its dynamics in Volyn region.Research methodology. The following research methods are used: comparative-geographical, mathematical-statistical, method of geoinformation modeling (using MapInfo Professional 8.0 SCP).The results of the research reflect the current urban tendencies in Volyn region, in particular, the unevenness of the settlement of the urban population through natural and economic factors. During the research period, the dynamics of the number of urban residents increased as a result of migration growth, and the percentage of urbanization in Volyn region stabilized. Currently, the number of urban population and the urbanization of Volyn region, in addition to natural reproduction of the population and intra-regional migration, have a significant impact on interregional and interstate migration flows. Since urbanization reflects contemporary socio-economic trends in the development of society, the issue of urban lifestyles remains among perspective research.Scientific novelty and practical significance. The course, trends and dynamics of urbanization processes in Volyn and other Ukrainian regions have become an important task on the way to improving the effectiveness of spatial planning, especially in terms of territorial and administrative reform in Ukraine.